1991
DOI: 10.1128/jvi.65.4.2056-2065.1991
|View full text |Cite
|
Sign up to set email alerts
|

Antigenic and genetic variation in cytopathic hepatitis A virus variants arising during persistent infection: evidence for genetic recombination

Abstract: Variants of hepatitis A virus (pHM175 virus) recovered from persistently infected green monkey kidney (BS-C-1) cells induced a cytopathic effect during serial passage in BS-C-1 or fetal rhesus kidney (FRhK-4) cells. Epitope-specific radioimmunofocus assays showed that this virus comprised two virion populations, one with altered antigenicity including neutralization resistance to monoclonal antibody K24F2, and the other with normal antigenic characteristics. Replication of the antigenic variant was favored ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
85
1

Year Published

1993
1993
2019
2019

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 190 publications
(88 citation statements)
references
References 36 publications
2
85
1
Order By: Relevance
“…The mechanism of the cytopathogenic effect (cpe) produced by the rapidly replicating HAV strains has been intensely investigated during the past few years to understand why wild type (wt) and cell culture adapted (cc) strains replicate slowly and are unable to induce cpe in these cell lines. These studies have revealed that the genome of the cpe-inducing (cp) strains contain point mutations, compared to the wt strains from which they were derived, scattered throughout the genome, as well as a 14-bp repeat in the 5 non-translated region (NTR), which harbors the internal ribosomal entry site or IRES (Lemon et al, 1991;Brack et al, 1998). The biological significance of these mutations for the rapid replication phenotype of the cp strains is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…The mechanism of the cytopathogenic effect (cpe) produced by the rapidly replicating HAV strains has been intensely investigated during the past few years to understand why wild type (wt) and cell culture adapted (cc) strains replicate slowly and are unable to induce cpe in these cell lines. These studies have revealed that the genome of the cpe-inducing (cp) strains contain point mutations, compared to the wt strains from which they were derived, scattered throughout the genome, as well as a 14-bp repeat in the 5 non-translated region (NTR), which harbors the internal ribosomal entry site or IRES (Lemon et al, 1991;Brack et al, 1998). The biological significance of these mutations for the rapid replication phenotype of the cp strains is not completely understood.…”
Section: Introductionmentioning
confidence: 99%
“…Some variants of measles virus in persistent infections are resistant to interferon (Carrigan & Knox, 1990). Variants of hepatitis A virus isolated from persistently-infected monkey cells were cytophatic (Lemon et al, 1991). The appearance of variants which evade immune surveillance has been reported for visna view of sheep (Stanley et al, 1988) and for equine infectious anaemia virus (Salinovich et al, 1986).…”
Section: Viral Genomes Of Persistent Infections Vary In Theirmentioning
confidence: 93%
“…Righthand (1991) showed that persistent non-lytic variants of echovirus 6 replicate. Lemon et al (1991) measured the rate of replication of hepatitis A virus in cultured cells.…”
Section: The Evolution Of Viruses Within Hostsmentioning
confidence: 99%
See 1 more Smart Citation
“…For all human hepatitis viruses, recombination has been exhaustively described. [78][79][80][81][82][83] The plethora of recently discovered viruses has enabled revisiting the occurrence of recombination events during the genealogy of human hepatitis viruses and their animal homologues.…”
Section: Envelopment Might Not Be Conserved Among Animal Hepatitis VImentioning
confidence: 99%